2020
DOI: 10.1002/smj.3125
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in speed of advancement: An empirical examination of top executives in the Fortune 100 firms

Abstract: Research summary We examine the advancement of women in executive roles in the ranks of the 10 highest executive positions in the Fortune 100 companies in 2001 and 2011. We find that women executives secured top executive positions faster than men, controlling for relevant individual attributes, and that the advantage of women with respect to men grew with the number of years they spent in the organization. The female advantage disappeared once companies had more than one high‐ranking female executive. We make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 74 publications
0
23
0
4
Order By: Relevance
“…Our results also have relevant regulatory implications. In particular, they suggest that the efforts to increase women's representation in competitive jobs should not only deal with entry and selection issues (e.g., Niederle et al, 2012; Sheridan & Milgate, 2005) but also address the less explored challenges associated with the retention of women in those positions and their upward mobility within the corporate hierarchy (Bonet et al, 2020). These considerations parallel recent evidence on women's career dynamics (Bertrand et al, 2010), showing that, despite initial comparable levels, the earnings of male and female MBAs tend to diverge over time due to career discontinuities and differences in labor supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also have relevant regulatory implications. In particular, they suggest that the efforts to increase women's representation in competitive jobs should not only deal with entry and selection issues (e.g., Niederle et al, 2012; Sheridan & Milgate, 2005) but also address the less explored challenges associated with the retention of women in those positions and their upward mobility within the corporate hierarchy (Bonet et al, 2020). These considerations parallel recent evidence on women's career dynamics (Bertrand et al, 2010), showing that, despite initial comparable levels, the earnings of male and female MBAs tend to diverge over time due to career discontinuities and differences in labor supply.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a thriving culture of diversity requires an enduring presence of women into top corporate positions. Unfortunately, the bulk of this literature has dealt almost exclusively with the entry and promotion of women into top corporate positions (e.g., Bonet et al, 2020;Cook & Glass, 2014;Smith et al, 2013). With few exceptions (Gayle et al, 2012;Keller et al, 2020), the determinants of female executives' exit from their corporate positions remain largely unexplored.…”
Section: Gender In Corporate Governancementioning
confidence: 99%
“…For example, Eagly et al (2020) show that, over the last 70 years, the belief that women are less competent than men has declined and possibly even reversed. At least two studies show that the gender pay gap has reversed for high potential women (Dreher et al, 2019; Leslie et al, 2017) and that women may advance through the executive ranks more quickly than their male counterparts (Bonet et al, 2020). Another study showed that board members from underrepresented groups might be more resilient to the corporate scandals in earning additional board seats given their in-demand status (Naumovska et al, 2020).…”
Section: All Leadership Must Be Inclusive and Equitablementioning
confidence: 99%
“…A legnagyobb vállalatok vezetőit vizsgálva azt is megállapíthatjuk, hogy a vezetés legfelsőbb szintjein alacsonyabb a nők aránya, mint a funkcionális vezetők szintjén (Bonet-Cappelli-Hamori 2020). Utóbbi tendenciák Magyarországra nézve is igaznak bizonyulnak: egy 2003-as, a hazai 50 legnagyobb cégből 16 kiválasztott vállalatot vizsgáló kutatás is rámutatott arra, hogy a vezetői hierarchiában fölfelé haladva a nők aránya egyre csökken.…”
Section: Nemek Közötti Különbségek a Bérekben éS A Vezető Pozíciók Be...unclassified